Linezolid-Induced Thrombocytopenia in Patients with Renal Impairment: A Case Series, Review and Dose Advice - S. R. E. Laarhuis; C. H. M. Kerskes; M. R. Nijziel; R. J. A. van Wensen; D. J. Touw (Drugs in R&D, 2024)
Abstract Background and Objective Oral linezolid is often used as alternative therapy for intravenous vancomycin. According to the current guidelines, no dose adjustment has to be made in case of renal impairment. Nevertheless, in our hospital we have seen several patients with renal impairment who developed linezolid-induced thrombocytopenia when linezolid was taken in the standard dose. In this case series and review we want to emphasize the necessity of reviewing the Dutch and international guidelines. Methods We describe five cases with renal impairment that developed linezolid-induced thrombocytopenia in our hospital. A PubMed literature review was conducted to identify other cases and find the optimal dosing regimen for these patients. Results Our cases join a long list of cases and available literature about linezolid-induced thrombocytopenia in patients with renal impairment. Less linezolid-induced thrombocytopenia was found, both in our cases and in the literature, after dose reduction of 50%. High linezolid trough concentrations were associated with a higher risk of linezolid-induced thrombocytopenia. Besides renal impairment, other risk factors for developing linezolid-induced thrombocytopenia were also identified, such as low body weight, high daily dose/kg, higher age, longer duration of therapy, low baseline count, malignity, low-dose aspirin and interacting co-medication. Conclusion Re-evaluation of the current dose advice is necessary. We advocate for a standard dose reduction to 50% after 2 days of standard dosing for all patients with an estimated glomerular filtration of <60 mL/min/1.73 m2. Besides this, therapeutic drug monitoring and thrombocytes monitoring may be executed weekly when patients have renal impairment or other risk factors for developing linezolid-induced thrombocytopenia.